Factors associated with nutritional status of children living in welfare homes in Selangor, Malaysia - A Rahim, Nur Nabilla (2016)
This cross-sectional study was conducted to determine the association between socio-demographic, psychological, dietary, and physical activity factors with BMI-for-age and Height-for-age among welfare home children in Selangor. While information on studied variables was obtained using self-administered questionnaires, height and weight were measured by trained researchers. BMI-for-age and Height-for-age were classified based on the WHO Growth Reference 2007. The study sample consisted of 307 school-going welfare home children (mean age of 13.0±2.7 years old) from 15 selected welfare homes, with 51.5% boys and 48.5% girls. There were three statuses of welfare home children in the study, including orphans (54.4%), abandoned children (23.8%), and children from problematic families (21.8%). The prevalence of overweight and obesity (23.1%) was three times higher than thinness and severe thinness (8.5%). The findings reported that age (r=0.169, p=0.003), satisfaction of body size and shape (r=0.551, p=0.0001), self-esteem (r=-0.112, p=0.049), and energy expenditure per kilogram body weight (r=-0.550, p=0.0001) were correlated with BMI-for-age. Besides that, there were differences in BMI-for-age by sex (t=-3.992, p=0.0001), ethnicity (F=5.358, p=0.001), children status (F=5.926, p=0.003), and perception of body weight status (F=6.523, p=0.0001), respectively. The prevalence of severe stunting and stunting was 13.6%. The findings reported that age (r=-0.128, p=0.024), satisfaction of body size and shape (r=0.117, p=0.040), trying new food (r=-0.133, p=0.020) and energy expenditure per kilogram body weight (r=-0.213, p=0.0001) were correlated with Height-for-age. The multiple linear regression analysis showed that girls (β=0.428), Malay (β=0.602) or Chinese (β=0.437), at an older age (β=0.150), abandoned (β=0.369), underestimated their body weight status (β=0.460), have higher dissatisfaction with their body size and shape (β=0.361), and have lower energy expenditure per kilogram body weight (β=-0.053) contributed to the variances in higher BMI-for-age (R2=0.566, F=48.515, p<0.05). Besides that, the multiple linear regression showed that respondents of younger age (β=-0.173), and low energy expenditure per kilogram body weight (β=-0.032) contributed to the variances in low height-for-age (R2=0.150, F=26.846, p<0.05). In conclusion, overweight and obesity problem was more prevalent than thinness and stunting problem among the welfare home children in Selangor. Hence, periodic assessment is essential to monitor their body weight status. The reported findings can be used as guidelines for planning nutrition intervention programs among welfare home children.